Aplicação de métodos e ferramentas de gestão dimensional em componentes de carrocerias de ônibus - Zilio, Tiago Muner (2014)
The product development process (PDP) must occur quickly and effectively, addressing the needs imposed by the various markets, in a short time. However, we know that engineering designs consider mathematically simplified information, which in many cases do not accurately represent reality, raising the risk of failure in product design. Whereas most projects go through a stage of dimensional specification, this document focuses on the concept Design Dimensional Control (DDC) and its application in a bus factory. To achive the objective proposed, concepts and tools required to use the method were discussed, being applied on the buses application. Understanding all aspects described, the method is detailed systematically, with conceptual emphasis. After it is performed a validation based on a real product application. The results met the proposed objectives, validating the same in the organizational context in which it was inserted.